INFLUENCE OF SURFACE MICRORELIEF PARAMETERS OF ELECTROMAGNETIC SHIELDS CONSTRUCTIONS BASED ON FOIL MATERIALS ON THEIR REFLECTION AND TRANSMISSION COEFFICIENTS - E. A. Almashat; O. V. Boiprav; L. M. Lynkou; N. I. Mukhurov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The research results of influence of the surface geometrical irregularities height of electromagnetic shields constructions made from foil materials based on aluminum on their electromagnetic radiation reflection and transmission coefficients values in frequency range 0.7…17 GHz are presented. The practical utilization ways of such constructions are proposed.